APPLICATION INNOVATION FOR MAKING POLICE RECORD CERTIFICATE (SKCK) IN THE LEGAL AREA OF POLRESTABES SEMARANG - Ayu Nafitaningrum; Retno Sunu Astuti (Journal of Public Policy and Management Review, 2021)
SKCK Online isn innovation made by the National Police Headquarters to be implemented in the police environment with the aim of making it easier for the public to organize SKCK. However, based on the data obtained, the public's interest in SKCK Online at Polrestabes Semarang is still very small. This study aims to determine how the innovation of SKCK Polrestabes Semarang and analyze what factors hinder the application of SKCK innovation in Polrestabes Semarang. This research is a qualitative descriptive study with interview and observation techniques. This research was analyzed by looking at the components of the SOP SKCK Polrestabes Semarang which included: service requirements, mechanisms and procedures, completion time, service fees, service products, handling complaints and suggestions, infrastructure, executive competence, number of implementers, service assurance. , product safety assurance and analysis. Rogers and Albury's public sector barriers to innovation. The results showed that the innovation of SKCK Online at Polrestabes Semarang City did not show a match between the old service mechanisms and procedures, the competence of the executors, and the number of implementers. And the factors inhibiting the implementation of SKCK Online innovation in Semarang City are influenced by excessive dependence on high performance, available technology, but are hampered by culture or organization, lack of rewards or incentives, inability to face risks and changes, budget constraints and planning, and is influenced by internal factors, namely the views of the community. Suggestions given are: make a division of tasks and tasks at the SKCK Service Center so that there is no impression of "odd jobs" due to unclear division of labor, need to recruit employees, change the print out display of proof of online registration by giving dates, provide special training to all implementing officers SKCK Online, provides rewards to SKCK Online implementing officers, creates special counters for SKCK Online users, collaborates with Dispendukcapil, continues to socialize SKCK Online